Use of crude glycerine and microbial inoculants to improve the fermentation process of Tifton 85 haylages - Cunha, Stefane S.; Orrico Junior, Marco A. P.; Reis, Ricardo A.; Orrico, Ana C. A.; Schwingel, Alice W.; Reis, Sirio D. S.; Silva, Mabio S. J. (Springer, 2019)
The increase in haylage production leads to the search for additives that improve its fermentation and nutritional value. This study aimed to assess the effect of adding crude glycerine and microbial additives on losses, fermentation parameters and nutritional value of haylage. The treatments were composed of three doses of crude glycerine (0, 60 and 120 g/kg forage) and three types of inoculation (control (distilled water), SIL (Lactobacillus plantarum 2.6x10(10) CFU/g and Pediococcus pentosaceus 2.6x10(10) CFU/g) and INC (Bacillus subtilis 2.0x10(9) CFU/g, Lactobacillus plantarum 8.0x10(9) CFU/g and Pediococcus acidilactici 1.0x10(10) CFU/g)). A negative linear effect was observed in the fibre fraction contents of the haylages as a function of crude glycerine addition, which contributed to similarly increasing dry matter in vitro digestibility coefficients. The use of inoculants also resulted in haylages with higher digestibility coefficients of 635.1 and 646.8 g/kg dry matter (DM) in the treatments inoculated with INC and SIL, respectively. Fermentation losses were reduced by adding crude glycerine and were not impacted by the microbial inoculants. Higher lactic acid productions were obtained as a function of crude glycerine doses. Acetic acid productions decreased from 29.3 g/kg DM to 19.2 g/kg DM between crude glycerine doses of 0 and 120 g/kg forage, respectively. SIL led to the highest lactic acid productions compared to INC and the control. Crude glycerine improves the fermentation parameters and nutritional value of haylages. However, the microbial inoculants had little impact on the parameters assessed.
Keywords: Cynodon spp; Glycerol; Nutritional value; Pre-dried